Athapascan fish drying racks with salmon, Alaska, ca. 1915 - Andrews, Clarence Leroy, 1862-1948
Salmon drying on wooden racks near river, ca. 1910-1920. Note from unidentified source: Indians drying salmon along the river last summer. Lower Yukon?